2017
DOI: 10.4196/kjpp.2017.21.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Acepromazine inhibits hERG potassium ion channels expressed in human embryonic kidney 293 cells

Abstract: The effects of acepromazine on human ether-à-go-go-related gene (hERG) potassium channels were investigated using whole-cell voltage-clamp technique in human embryonic kidney (HEK293) cells transfected with hERG. The hERG currents were recorded with or without acepromazine, and the steady-state and peak tail currents were analyzed for the evaluating the drug effects. Acepromazine inhibited the hERG currents in a concentration-dependent manner with an IC50 value of 1.5 µM and Hill coefficient of 1.1. Acepromazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It is also possible that acepromazine may have played a role. An experimental study in humans reported that acepromazine may have a potentially arrhythmogenic action through the inhibition of human ether-à-go-go-related gene (hERG) potassium channels in cardiac tissues and the prolongation of QT intervals ( 61 ). We elected to use methadone as premedication in the dogs in this study as it is the only full opioid agonist currently licensed in this species in the U.K. and Europe, and we wanted to produce data relevant to clinical veterinary practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that acepromazine may have played a role. An experimental study in humans reported that acepromazine may have a potentially arrhythmogenic action through the inhibition of human ether-à-go-go-related gene (hERG) potassium channels in cardiac tissues and the prolongation of QT intervals ( 61 ). We elected to use methadone as premedication in the dogs in this study as it is the only full opioid agonist currently licensed in this species in the U.K. and Europe, and we wanted to produce data relevant to clinical veterinary practice.…”
Section: Discussionmentioning
confidence: 99%